Vanilla cameroniana (Orchidaceae, Vanilloideae), a new species from French Guiana and new records from the Guiana Shield - Damián-Parizaca, Alexander; Mitidieri-Rivera, Nicole (Phytotaxa, 2023)
In this study, a new species of Vanilla from French Guiana is described with detailed illustrations, photographs, and distribution. Vanilla cameroniana honors Kenneth M. Cameron, a distinguished professor at the University of Wisconsin-Madison, for his contributions to our understanding of the subfamily Vanilloideae. The new species is placed within Vanilla subgenus Xanata, due to its distinctive penicillate callus and lip margins connate to the column. Vanilla cameroniana can be distinguished from V. appendiculata, a morphologically similar species by the broader leaves up to 12 cm wide (vs. 5.9 cm), axillary inflorescence (vs. apical), narrow linear petals, 0.2–0.3 cm wide (vs. narrowly lanceolate, 0.5–0.8 cm), unlobed lip (vs. trilobed), and sub-quadrate apex (vs. sub-acute) with a trullate-shaped structure close to the apex made of short appendages (vs. long lombricoid appendages). Detailed morphological comparisons are provided for other superficially similar species. Additionally, based on herbarium collections V. sprucei, and V. dressleri are newly recorded from the Guiana Shield, and a geographic range expansion is proposed for Vanilla corinnae. Our findings highlight the importance of conservation efforts of fragile ecosystems such as swamps in the Guiana Shield.